2021
DOI: 10.1002/cam4.3791
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of single patient investigational new drug (IND) requests in pediatric oncology

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There is a strong consensus that the involvement of children and adolescents in clinical trials is the clear priority and all efforts should be made to facilitate access to trials. However, currently there are children who receive innovative medicines outside clinical trials and the related data are not captured [48,49]. Furthermore, these data should be made available for prescribers and families and useable for regulatory purposes.…”
Section: Real World Evidence (Rwe)mentioning
confidence: 99%
“…There is a strong consensus that the involvement of children and adolescents in clinical trials is the clear priority and all efforts should be made to facilitate access to trials. However, currently there are children who receive innovative medicines outside clinical trials and the related data are not captured [48,49]. Furthermore, these data should be made available for prescribers and families and useable for regulatory purposes.…”
Section: Real World Evidence (Rwe)mentioning
confidence: 99%
“…Similarly, in the United States, 11% of patients undergoing tumor profiling under the Veterans Affairs program received off‐label prescriptions for targeted therapies 19 . The increase in pediatric precision oncology 14 is illustrated by the 48.3% of requests reported in this work that were based on the presence of a specific molecular driver or molecular target.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, as most InMPs are studied on adults first, EAP might be particularly beneficial for pediatric populations, who might otherwise face substantial delays before treatments for life-threatening rare cancers and diseases become available. A retrospective analysis of all single patient IND applications from a single pediatric oncology institution over a 2-year period reported that the FDA approved all 171 submitted requests; lack of a pediatric clinical trial (65%) was the most common reason for EAP application ( 29 ).…”
Section: Discussionmentioning
confidence: 99%